Quality corner: Safely using cephalosporins in almost all patients with penicillin allergies: Mini-review and suggested protocol to improve efficacy and surgical outcomes - Teresa K.L. Boitano; Abinash Virk; J. Michael Straughn Jr; Sean C. Dowdy (Elsevier, 2024)
Surgical site infections (SSI) are one of the most common gynecologic oncology postoperative complications and they have a significant deleterious impact on the healthcare system and in patients' outcomes. Cefazolin is the recommended antibiotic in women undergoing gynecologic surgical procedures that require that require prophylaxis. However, 10-20% of patients may report a penicillin allergy which can result in administration of a less effective antibiotic. This quality review evaluated the literature around this common perioperative issue and demonstrated that healthcare teams should consider the implementation of a protocol to safely use cefazolin in most patients with a penicillin allergy. Overall, literature shows this is a safe adjustment and would improve antimicrobial stewardship, decrease SSI rates, avoid acute kidney injury, and increase cost savings.